Organizational climate, organizational commitment, job satisfaction, and employee performance - Irwan Sugiarto (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2018)
The purpose of this study was to examine the relationship between organizational climate, organizational commitment, job satisfaction, and employee performance. Particularly, we examine the effect of organizational climate and organizational commitmenton job satisfaction. Furthermore, we also test the effect of job satisfaction on employee performance.Results of path analysis on 90 respondents showsopports for all hypotheses. Partially, organizational climate and organizational commitment have positive effect on job satisfaction. Simultaneously, organizational climate and organizational commitment positivelyaffect job satisfaction. In addition, job satisfaction has positive effect on employee performance.